2012
DOI: 10.1111/j.1740-0929.2012.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen balance during compensatory growth when changing the levels of dietary lysine from deficiency to sufficiency in growing pigs

Abstract: Two experiments were conducted to elucidate the nitrogen (N) balance of pigs exhibiting compensatory growth when changing the dietary lysine levels from deficiency to sufficiency. Experiment 1 elucidated whether pigs exhibited compensatory growth with dietary lysine sufficiency. Twenty 6-week-old males were assigned to one of two treatments: control and LC (lysine and control). Control pigs were fed a control diet throughout the 24-day experimental period, whereas LC pigs were fed a low lysine diet until day 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…We prepared two diets: a control diet with 1.15% lysine and a low-lysine diet in with 0.73% lysine (Ishida et al 2012). The diets were iso-protein and iso-energetic, meaning both diets had the same concentrations of all essential amino acids except lysine and met the nutritional requirements (NRC, 1998).…”
Section: Nitrogen Balance During Compensatory Growth With Changing DImentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared two diets: a control diet with 1.15% lysine and a low-lysine diet in with 0.73% lysine (Ishida et al 2012). The diets were iso-protein and iso-energetic, meaning both diets had the same concentrations of all essential amino acids except lysine and met the nutritional requirements (NRC, 1998).…”
Section: Nitrogen Balance During Compensatory Growth With Changing DImentioning
confidence: 99%
“…In this paper, we describe the results of our first study on compensatory growth induced by lysine in pigs (Ishida et al 2012). We then describe our studies using a rat model (Ishida et al 2011) and an in vitro model with cultured skeletal muscle cells (Ishida et al 2013) to elucidate the mechanisms of compensatory growth after restriction-realimentation with lysine alone.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that changing from a lysine-deficient diet to a lysine-sufficient diet induced compensatory growth in rats and pigs. 2,3) These studies demonstrated for the first time that changing dietary levels of a single essential amino acid from deficient to sufficient induced compensatory growth in growing animals.…”
mentioning
confidence: 99%
“…2,3) It has been reported that ad libitum feeding after restriction feeding increased plasma IGF-I concentrations to the control levels in young bulls and pigs. 4,5) IGF-I stimulates hypertrophy in myotube and skeletal muscle, [6][7][8] but the role of IGF-I during compensatory growth remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation